Short- and Long-Term Cause of Death in Patients Treated with Primary PCI for STEMI - Tarique Ahmed, Tahir Saghir, Nasir Ali, Shahzad, Faraz Farooq Memon, Abdul Hakeem Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: While the long-term cause of death in patients with STEMI is still undetermined, short-term mortality in patients experiencing PCI has been well-researched. Aims and Objectives: This study set out to investigate the connection among the time and cause of mortality rates in patients with STEMI who were receiving Primary Percutaneous Coronary Intervention. Materials and Methods: In 934 continuous patients with STEMI (age 60 ± 12 years, 72 per cent males) cured with primary PCI, the time and fatality were tracked using a centralized civil registration process, client files, and death cause and public disease registries with proper record linkage. Results: An average of 8 months was followed up with patients. 101 people passed away out of a total of 934 patients. Anoxic brain injury and cardiogenic shock following cardiac arrest were the two primary causes of death in the 1st1 30 days. The death rate was independently predicted by culprit vessel size, age, and flow, the prevalence of heart problems and Mellitus, and age. The yearly cardiac death rate is a little less than 1.5 per cent after thirty days. In 65 per cent of instances, non-cardiac mortality causes occurred after 30 days (mainly pulmonary diseases and malignancies). The death rates for all causes (including cardiac) at 30 days, 6 months, and over were 7.8 per cent (7.2 per cent), 11.2 (8.1 per cent), and 23.2 (13.7 per cent), accordingly. Conclusions: Patients with a good prognosis who survive the first month following a STEMI cured with PPCI have a less than 1.5 per cent monthly risk of subsequent cardiac mortality. Most of these individuals’ later deaths occur from reasons other than cardiac ones. Keywords: Percutaneous Coronary Intervention, Cause of Mortality, Acute MI, Follow-up Study